Design and Fabrication of a Composite Energy Absorber - Hamid Reza Shalian; Mohammad Hossein Alaee; Jafar Eskandari Jam; Mohsen Heydari Beni; Majid Eskandari Shahraki; Naser Asiaban (International Journal of Advanced Design and Manufacturing Technology, 2020)
In this paper, the quasi-static test and the damage of the thin-walled composite cylinder were numerically simulated using ABAQUS. Then, a comparison was made between the results of this simulation and those obtained from experimental studies followed by their validation. In the next step, several parameters affecting the energy absorption rate including outer diameter-to-cylinder height ratio, thickness-to-outer diameter ratio, and angle of damage initiation mechanism were selected. They were optimized by modelling different states in ABAQUS. The number of tests is reduced by the design of experiments using response surface methodology and the optimal specimen is extracted by this software. Finally, optimum adsorbent is fabricated and tested. Considering enhanced energy absorption, increased mean reaction force, and reduced initial maximum force, the optimal design parameters include the inner diameter-to-cylinder height ratio of 0.2, thickness-to-inner diameter ratio of 0.1, and angle of damage initiation mechanism of 45°.